Pilot study-based sharing system design method. Issue 1 (2022) - Umeda, Yasushi; Ishida, Ryo; Miyake, Gaku; Kishita, Yusuke; Matsuda, Genichiro; Tajima, Akio
Abstract: To achieve sustainability, it is necessary to change the value proposition method. This paper proposes a pilot study-based sharing system design method, which supports the finding of solutions for sharing services by focusing on the balance between demand and supply. A case study was conducted that involved designing a localized bike-sharing system. The proposed demand forecast model estimated the demand with an error of less than 15% owing to the execution of the pilot study and user segmentation. A service plan that satisfies the requirements in terms of availability, user cost, and profitability was achieved.